Corporate bankruptcy : economic and legal perspectives / edited by Jagdeep S. Bhandari, Lawrence A. Weiss. - Bhandari, Jagdeep S.; Weiss, Lawrence A. (Lawrence Alan) (Cambridge University Press, 1996)
This collection is the first comprehensive selection of readings focusing on corporate bankruptcy. Its main purpose is to explore the nature and efficiency of corporate reorganisation using interdisciplinary approaches drawn from law, economics, business, and finance. Substantive areas covered include the role of credit, creditors' implicit bargains, non-bargaining features of bankruptcy, workouts of agreements, alternatives to bankruptcy, and proceedings in countries other than the United States, including the United Kingdom, Europe, and Japan.